PERAN INSPEKTORAT DAERAH KABUPATEN NIAS SELATAN DALAM MELAKUKAN PENGAWASAN PENGELOLAAN KEUANGAN DESA - Sama Daya Ndruru (Jurnal Panah Hukum, 2023)
Village financial management is carried out by the village government, in managing village finances there is misuse or not on target. So with that in mind the Regional Inspectorate of South Nias Regency has a very important role in overseeing the management of village finances managed by the village head. To overcomen this problem, the Regional Inspectorate carries out activities in the from of reviews, monitoring, evaluation, Inspektions and other supervision. In accordance with Articel 6 of the Regulation of the Minister of Home Affairs Number 73 of 2020 concerning supervision of Village Financial Management This type of research is sociological law or it can be called empirical research which is research to find theories about existing processes in the field, which examines the applicable legal provisions and what happens in reality in society. So researchers are trying to examine the facts that exist in society with the intention of knowing how thw role of the Inspectorateis canrried out in supervising village financial management. The infrastructure of the South Nias District Inspectorate is inadequate, resulting in limittantios in carrying out village Financial management supervision activities, with a total of 459 village and 35 sub-districts in South nias district. With that, the researcher suggests to the South Nias Regency Government to pay attention, so that supervision of village Financial management goes according to existing regulations